Pendampingan Penerapan Good Agricultural Practices (GAP) pada Budidaya Kelapa Sawit di Desa Penyeladi, Pana, Kec. Kapuas, Kabupaten Sanggau, Kalimantan Barat - Arief Panca Putra; Bagus Nugroho; Subakho Aryo Saloko (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2025)
Peneladi Village, Pana, Kapuas District, Sanggau Regency, West Kalimantan, is a center for oil palm plantations with high production potential. However, most farmers still rely on conventional cultivation methods that do not fully adhere to Good Agricultural Practices (GAP) standards. This impacts low productivity, the quality of fresh fruit bunches (FFB), and environmental sustainability. This community service activity aims to provide technical assistance and education on the application of GAP in oil palm cultivation, including land management, balanced fertilization, integrated pest management (IPM), and timely harvesting. Implementation methods include outreach, training, demonstration plots (demplots), and field assistance. The activity results showed an 85% increase in farmers' knowledge and skills based on pre- and post-test evaluations, as well as the implementation of more environmentally friendly and efficient cultivation practices. Farmers began implementing a fertilizer system based on soil analysis results, proper frond pruning, and mechanical weed control to reduce herbicide use. This activity contributed to increasing farmer awareness of the importance of sustainable production and environmental management. Going forward, it is hoped that GAP implementation can be consistently implemented to increase oil palm productivity in Penyeladi Village, maintain the quality of fresh fruit bunches (FFB), and preserve ecosystem sustainability.